Estudo para reúso de efluentes de estações de tratamento de esgoto na irrigação - Goellner, Emanuelle (2010)
The reuse of domestic sewage effluent should be an alternative for those situations where the scarcity of water exists. The reuse of wastewater from treatment systems has enormeous potential to irrigation of backyards and public parks. A study to assess the viability of this reuse in irrigation of backyards was done, taking into account some quality parameters and the behaviour of faecal coliform bacteria after the irrigation of a greenfield in terms of surviving and microbiological risk to human exposure. The parameters were compared with the international quality guidelines for reuse, and the bacterial counting was done in the laboratory assays to determine the surviving of the faecal coliforms in the grass of a greenfield irrigated with the effluent of the two wastewater systems studied. The results showed differences between the quality parameters of the two systems, with high variability in their values and the aim of pre-treatment before the reuse must be considered. In relation of the microbiological standards, the field trials, with one or three successive spraying, showed that the bacterial coliforms counts decreased in the both experimental conditions to values below to the limits requirements for human health protection. In the trials of the store conditions, the behaviour of the bacterial populations was distinct, with the counts of faecal coliforms decreasing substantially with the time of storing to the anaerobic reactor, whereas these counts in the stabilization ponds system had a significant increase of the bacterial population until of the 21 day of studying, decreasing soon after , but with high values to bacterial counting